ANALISIS SISTEM PENGENDALIAN MANAJEMEN DALAM UPAYA MENINGKATKAN DAYA SAING : (STUDY KASUS PADA TOSERBA BORMA MAJALAYA) - Delia; Mega Sandy; Reva Dwina Sefira; Andre Yulianto (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2020)
Management control can be interpreted as a process to ensure that human, physical, and technologikal resources are allocated to achieve the goal of a company. The goal is to make a profit. However, challenges or problems arise from within the company relating to human resources and problem that arise from external companies, namely competitiveness were it is to maintain continuity of the company. The purpose of this study was to determine the aplikation of management control systems, the effectiveness of management control system, and strategies in increasing competitiveness TOSERBA BORMA MAJALAYA . The method used is descriptive qualitative method. This is evident that the planning carried out by the management of TOSERBA BORMA MAJALAYA is going well, as well as effective and efficient implementation, and there is an evaluation to continuously improve the system inmanagement control so as to create significant competitiveness so that it cant continue to exist and compete with competitor.